2018
DOI: 10.5935/medicalexpress.2018.mo009
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pneumomediastinum in dermatomyositis: a case series and literature review

Abstract: OBJECTIVES:To describe a case series of spontaneous pneumomediastinum in dermatomyositis and to review the literature. METHODS:This was a retrospective single-center case series, reporting 9 patients with pneumomediastinum and defined dermatomyositis, followed from 2005 to 2017. RESULTS: Median age of patients: 33 years; cutaneous and pulmonary involvement in all cases; constitutional symptoms in 88.8% of patients; involvement of the joints in 11.1%, gastrointestinal tract in 44.4%, and muscles in 77.7%; subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…11 Several cases of spontaneous pneumomediastinum were reported in patients with DM in the literature. 6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Similar to our patients, pneumomediastinum was reported in cases of DM and amyopathic DM, 11 occurred at a widely variable range of disease duration, 6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and was associated with variable outcomes from complete recovery 11 to death. 5,14,31,32 Pneumomediastinum occurred prior to (as our second patient), coinciding with, or after (as our first patient) pulmonary involvement.…”
Section: Reference To Relevant Literaturesupporting
confidence: 83%
See 3 more Smart Citations
“…11 Several cases of spontaneous pneumomediastinum were reported in patients with DM in the literature. 6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Similar to our patients, pneumomediastinum was reported in cases of DM and amyopathic DM, 11 occurred at a widely variable range of disease duration, 6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and was associated with variable outcomes from complete recovery 11 to death. 5,14,31,32 Pneumomediastinum occurred prior to (as our second patient), coinciding with, or after (as our first patient) pulmonary involvement.…”
Section: Reference To Relevant Literaturesupporting
confidence: 83%
“…Subcutaneous emphysema has also been reported in approximately 55.5% of cases of DM. 24 Though several case reports, case series, and review articles on DM and pneumomediastinum were reported in the literature, 6,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] only a few cases of DM had both pneumomediastinum and emphysema. 5,6,13,16,[18][19][20][21][22][25][26][27][33][34][35][36][37][38][39] Table 1 summarizes the main clinical features, treatment strategies, and outcomes of these cases.…”
Section: Reference To Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations